Penatalaksanaan Fisioterapi pada Pasien dengan Brachial Plexus Injury Sinistra di RSUP DR Sardjito Yogyakarta - Atmaja, Fifit Fidya, Agus Widodo, S.Fis, M.Fis, Wijianto, SSt.Ft., M.Or, Isnaini Herawati, S.Fis, M.Sc (2017)
PHYSIOTHERAPY MANAGEMENT IN PATIENT WITH BRACHIAL PLEXUS INJURY SINISTRA IN RSUP DR SARDJITO YOGYAKARTA (Fifit Fidya Atmaja, 2017, 44 pages) Abstract Background: Brachial plexus injury is an injury of the brachial plexus often caused by trauma. These traumas are often traction or excessive withdrawal or avulsion. Brachial Plexus Injury may affect motor and sensory function in the area it supplies. The most common disorders are muscle atrophy, sensory impairment, and decreased muscle strength that will be followed by the patient's limitation in daily functional activities. Purpose: To find out the management of physiotherapy using Physiotherapy modalities in the form of Electrical Stimulation (ES) and exercise therapy to prevent the occurrence of increased muscle atrophy, increased muscle strength, range of motion and daily functional activity of the patient. Result: After the treatment for 6 times obtained the results of muscle volume T1: 25 cm, constantly T6: 25 cm. Assessment for the muscle strength of flexor shoulder T1: 3, constantly T6: 3, extensor shoulder T1: 2, constantly T2: 2, abductorshoulder T1: 3, constantlyT6: 3, adductor shoulder T1: 3, constantly T6: 3, external rotator shoulder T1: 2, constantly T6: 2, internal rotator shoulder T1: 2, constantly T6: 2, flexor elbow T1: 3, constantly T6: 3, extensor elbow T1: 3, constantly T6: 3, supinator elbow T1: 2, constantly T6: 2, pronator elbow T1: 2, constantly T6: 2, flexor wrist T1: 3, constantly T6: 3, extensor wrist T1: 1, constantly T6: 1, radial deviator wrist T1: 1, constantly T6: 1, ulnar deviator wrist T1: 1, constantly T6: 1, flexor finger T1: 2, constantly T6: 2. Range of Motion (ROM) shoulder S: T1: 30o - 0o - 70oconstantly T6: 30o - 0o - 70o, F: T1: 80o - 0o - 20o, constantly T6: 80o - 0o - 20o, R: T1: 10o - 0o - 20o, constantly T6: 10o - 0o - 20o, ROM elbow S: T1: 0o - 0o - 100o, constantly T6: 0o - 0o - 100o, R: T1: 25o - 0o - 10o, constantly T6: 25o - 0o - 10o, ROM wrist S: T1: 0o - 0o - 25o, constantly T6: 0o - 0o - 25o, F: T1: 0o - 0o - 0o, constantly T6: 0o - 0o - 0o, ROM finger MCP I flexor T1: 0o - 35o, constantly T6: 0o - 35o, MCP II - V flexor T1: 0o - 0o, constantly T6: 0o - 0o, DIP II - V flexor T1: 0o - 50o, constantly T6: 0o - 50o, PIP II - V flexor T1: 0o - 20o, constantly T6: 0o - 20o. Assessment of daily functional activity with the score T1: 31, constantly T6: 31. Conclusion: Management of physiotherapy with Electrical Stimulation (ES) and exercise therapy can prevent increased muscle atrophy, but no changes in muscle strength, range of motion, and daily functional activity. Keyword: Brachial Plexus Injury, Electrical Stimulation, exercise therapy.